2021
DOI: 10.3389/fpsyt.2021.698954
|View full text |Cite
|
Sign up to set email alerts
|

A Treatment-Response Comparison Study of Resting-State Functional Magnetic Resonance Imaging Between Standard Treatment of SSRI and Standard Treatment of SSRI Plus Non-dominant Hand-Writing Task in Patients With Major Depressive Disorder

Abstract: Background: Researches have recently shifted from functional/structural imaging studies to functional connectivity (FC) studies in major depressive disorder (MDD). We aimed to compare treatment response of two treatment groups before and after treatment, in terms of both with psychiatric evaluation scales and resting-state functional connectivity (RSFC) changes in order to objectively demonstrate the possible contribution of the non-dominant hand-writing exercise (NHE) effect on depression treatment.Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(70 reference statements)
0
1
0
1
Order By: Relevance
“…Moreover, in accordance with previous findings ( 26 , 45 47 ), the present study reported that patients with MDD showed abnormal neural activity in brain regions within the default mode network. These regions—the thalamus, precuneus, and parahippocampus—are important components in the default mode network ( 48 ). The thalamus, as a hub connecting the cortex and subcortical regions, is thought to be the transformation center for all neural signals from bodily sensations projected to the cerebral cortex ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in accordance with previous findings ( 26 , 45 47 ), the present study reported that patients with MDD showed abnormal neural activity in brain regions within the default mode network. These regions—the thalamus, precuneus, and parahippocampus—are important components in the default mode network ( 48 ). The thalamus, as a hub connecting the cortex and subcortical regions, is thought to be the transformation center for all neural signals from bodily sensations projected to the cerebral cortex ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Esto se puede constatar con el estudio realizado en la Universidad de Bezmialem VAKIF en Turquía (Boyraz et al, 2021), este estudio tuvo una población de 26 mujeres con características sociodemográficas similares con sintomatología de depresión mayor, las cuales fueron divididas en dos subgrupos de forma aleatoria de 13 participantes cada uno teniendo como objetivo comparar la respuesta del tratamiento. Las pruebas neuropsiquiatras posterior al tratamiento dieron resultados significativos diferentes en ambos grupos, evidenciando de manera objetiva la contribución positiva de la técnica EMDR en el tratamiento de la depresión en el grupo seleccionado, aunque ambos grupos mantuvieron un tratamiento médico estándar.…”
Section: Discussionunclassified